2022
DOI: 10.3389/fnut.2021.788965
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study: Nutritional and Preclinical Safety Investigation of Fermented Hispidin-Enriched Sanghuangporus sanghuang Mycelia: A Promising Functional Food Material to Improve Sleep

Abstract: Sleep disturbances have been the hallmark of the recent coronavirus disease 2019 pandemic. Studies have shown that once sleep is disrupted, it can lead to psychological and physical health issues which can, in turn, disrupt circadian rhythm and induce further sleep disruption. As consumers are trying to establish healthy routines, nutritional and preclinical safety investigation of fermented hispidin-enriched Sanghuangporus sanghuang mycelia (GKSS) as a novel food material for spontaneous sleep in Sprague-Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Sanghuangporus spp., also known as Phellinus or Inonotus in some of the literature and some areas worldwide, is a perennial genus of edible mushrooms widely distributed in boreal forests in East Asia, especially in subtropical and tropical areas, holding profound pharmaceutical potential [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. These medicinal mushrooms, as illustrated in Figure 1 , have been popular in oral use since ancient times in countries such as China, Korea, and Japan [ 4 , 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sanghuangporus spp., also known as Phellinus or Inonotus in some of the literature and some areas worldwide, is a perennial genus of edible mushrooms widely distributed in boreal forests in East Asia, especially in subtropical and tropical areas, holding profound pharmaceutical potential [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. These medicinal mushrooms, as illustrated in Figure 1 , have been popular in oral use since ancient times in countries such as China, Korea, and Japan [ 4 , 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Entering modern times, pharmaceutical research has demonstrated multiple functions of Sanghuangporus spp., including the ability to improve blood circulation, scavenge free radicals, demonstrate anti-inflammatory effects, anti-carcinogenesis, antioxidative abilities, immunomodulatory effects, antidiabetic activities, antimicrobial abilities, and antiaging effects [ 2 , 4 , 9 , 14 , 20 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 ]. Some research has also provided evidence of antigout, sleep-improving, neuroprotective, and hepatoprotective activities [ 3 , 30 , 31 , 32 ]. Despite their prolonged use in history, research progress on the application of these mushrooms has been slow, mainly due to the following factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the phytochemical constituents of S. sanghuang —hispidin, the yellow polyphenol pigment, displayed excellent antioxidant and anti‐obesity properties 15 . In our previous study, we observed that hispidin‐enriched S. sanghuang can upregulate nuclear factor erythroid 2‐related factor 2 (Nrf2) in a dosage‐dependent manner 16 . Deficiency of Nrf2 expression has been reported as a vital marker associated with sarcopenia development in vivo 17 .…”
Section: Introductionmentioning
confidence: 99%
“…15 In our previous study, we observed that hispidin-enriched S. sanghuang can upregulate nuclear factor erythroid 2-related factor 2 (Nrf2) in a dosage-dependent manner. 16 Deficiency of Nrf2 expression has been reported as a vital marker associated with sarcopenia development in vivo. 17 Clinical study also showed that the Nrf2-antioxidant response element (ARE) pathway is impaired in older adults (63 ± 1 years) and the benefit of exercising is less effective when compared with the young adult (23 ± 1 years).…”
Section: Introductionmentioning
confidence: 99%